1995
DOI: 10.1007/bf00020185
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the betaine aldehyde dehydrogenase gene in barley in response to osmotic stress and abscisic acid

Abstract: When subjected to salt stress or drought, some vascular plants such as barley respond with an increased accumulation of the osmoprotectant glycine betaine (betaine), being the last step of betaine synthesis catalyzed by betaine aldehyde dehydrogenase (BADH). We report here cloning and characterization of BADH cDNA from barley, a monocot, and the expression pattern of a BADH transcript. An open reading frame of 1515 bp encoded a protein which showed high homology to BADH enzymes present in other plants (spinach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
125
1
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 221 publications
(134 citation statements)
references
References 40 publications
2
125
1
3
Order By: Relevance
“…It is well documented that ABA is an essential mediator in plant response to environmental stresses [25]. ABA and drought treatments can trigger an increase in BADH mRNA levels and the content of BADH protein in barley leaves at low temperature, but the results showed a low level accumulation of GB [12], [26]. Naidu et al [27] reported that concentration of accumulated betaine in cold-stressed wheat seedlings increased more than doubled in the controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that ABA is an essential mediator in plant response to environmental stresses [25]. ABA and drought treatments can trigger an increase in BADH mRNA levels and the content of BADH protein in barley leaves at low temperature, but the results showed a low level accumulation of GB [12], [26]. Naidu et al [27] reported that concentration of accumulated betaine in cold-stressed wheat seedlings increased more than doubled in the controls.…”
Section: Discussionmentioning
confidence: 99%
“…CMO was assumed to be unique among plant oxygenases [6], [8]. The second step of GB synthesis is mediated by betaine aldehyde dehydrogenase (BADH) [1], which has been well documented in amaranth [2], [9] and other plants [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The aldehyde dehydrogenase superfamily comprises seven enzymes of bacterial and plant origin with known involvement in the synthesis of the osmoprotectant glycine betaine from its precursor glycine betaine aldehyde. These are the BetB proteins from E. coli (13) and Rhizobium meliloti (41) and betaine aldehyde dehydrogenases from plants (Spinacia oleracea, Beta vulgaris, Atriplex hortensis, Sorghum bicolor, and Hordeum vulgare) involved in the cellular adaptation to salinity and drought (24,36,53,56,57). The B. subtilis enzyme exhibits 39% sequence identity to the BetB proteins from E. coli and R. meliloti.…”
Section: Vol 178 1996 Glycine Betaine Synthesis In B Subtilis 5123mentioning
confidence: 99%
“…Recombinant ALDH2a protein shows acetaldehyde oxidization activity in vitro, suggesting a function in plant tolerance under anaerobic conditions . Betaine aldehyde dehydrogenases (BADHs), members of the ALDH10 family, have been intensively studied for their well-documented potential against environmental stresses, such as salinity, drought and cold (Weretilnyk and Hanson 1990;McCue and Hanson 1992;Ishitani et al 1995;Wood et al 1996;Nakamura et al 1997). Generally, BADH transcription in higher plants is induced in response to osmotic stress and its defined role is to catalyze the second step reaction in a two-step oxidation of choline via an intermediate form of betaine aldehyde in the biosynthetic pathway of the osmolyte glycine betaine (Chen and Murata 2002).…”
Section: Introductionmentioning
confidence: 99%